Starring Adele Astaire : a novel - Knight, Eliza (William Morrow, an imprint of HarperCollinsPublishers, 2023)
Adele Astaire was a glittering, glamorous star, dancing with her brother, Fred, endearing herself to audiences from New York to London. But although she is toasted by royalty and beloved by countless fans, Adele Astaire has dreams of a loving husband and a houseful of children. And when she meets Lord Charles Cavendish, her wishes may just come true, but at what cost? Ever since Violet Wood could walk she's wanted to dance on the London stage. Befriended by Adele, filled with ambition, she is more than willing to make the sacrifices it will take to become a star herself, and her rags-to-riches hopes are within reach. But the road to fame is never easy. From the fast-paced world of roaring 20s New York to the horrors and sacrifice of wartime London, Adele's and Violet's lives intertwine, and each must ask themselves is fame worth the price you must pay?